EVALUATING THE EFFICACY OF DIGITAL AUTHENTIC MATERIALS: CHALLENGES IN TAILORED LANGUAGE LEARNING IN ESP CONTEXTS - Khainur Jannah; Dadang Sudana; Fathin Anjani Hilman (Getsempena English Education Journal)
This research analyzes the effectiveness of tasks based on digital authentic materials (DAM) in custom language instruction in English for Specific Purposes (ESP). The study analyzes the barriers to applying DAM to enhance ESP learners' linguistic and professional skills. A case study approach was used with data triangulation to address the problems associated with using DAM in self-paced learning programs. The participants consisted of six ESP lecturers across diverse disciplines at one public university with established ESP programs across various faculties. The results indicate that although DAM enhances engagement and contextual understanding, issues of content scope, technological barriers, and learner diversity regarding proficiency levels are still present. This study advances the discourse on the optimal use of digital authentic materials by considering the parameters defined by ESP frameworks, particularly for pedagogical strategies geared towards efficient language acquisition customization. The authors offer suggestions that can be put into immediate action by educators and material creators who want to mitigate the concerns reinforced in this study while trying to harness the full capabilities of digital tools resources within an ESP teaching and learning context.